Enhanced biological control of root-knot nematode, Meloidogyne incognita, by combined inoculation of cotton or soybean seeds with a plant growth-promoting rhizobacterium and pectin-rich orange peel - Hassan, Mohammad K.; Lawrence, Kathy S.; Sikora, Edward J.; Liles, Mark R.; Kloepper, Joseph W. (Journal of nematology, 2021)
LC-MS analysis of plant growth-promoting rhizobacterium (PGPR) AP203 supernatants indicated the presence of nematode-inhibiting compounds that increased in abundance when AP203 was grown on orange peel. J2 were incubated with AP203 spores and orange peel, spores alone, orange peel alone, or with a non-inoculated control, and the combination of AP203 with orange peel resulted in 94% mortality of juveniles ( ≤ 0.05). The J2 mortality rate for alone was 53%, compared to 59% mortality with orange peel, and the non-inoculated control exhibited 7% mortality. When tested on soybeans raised in a greenhouse, it was observed that when grown in the presence of orange peel, AP203 culture broth, cell suspension or supernatant reduced the numbers of eggs per g of root at 45 days after planting (DAP) compared to inoculated controls in soybean and cotton ( ≤ 0.05). Likewise, soybean root length and fresh root weight significantly increased after inoculation with AP203 amended with orange peel. In cotton, shoot and root length significantly increased after inoculation with cell pellets of AP203 amended with orange peel compared to the inoculated control. These data indicate that AP203 responds to growth on pectin-rich orange peel by production of biologically active secondary metabolites that can promote plant growth and inhibit root-knot nematode viability.